26. Definitive repair of pulmonary atresia with ventricular septal defect using valved conduit for low body weight infant - Vinh, Tran Quang; Truong, Nguyen Ly Thinh; Hung, Doan Quoc (Tạp chí Nghiên cứu Y học, 2022)
Pulmonary atresia with ventricular septal defect is a complex congenital heart defect whose management varies depending on the anatomy of pulmonary circulation and surgeon’s preferences. The surgical outcomes of complete repair in small infants and neonates in Vietnam have been seldomly reported. We reported our medium-term results of complete repair of this complex lesion using valved conduit in infants and neonates at our institution. The study included 25 patients with the body weight of less than 5kg who underwent definitive repair using valved conduit between January 2016 and December 2021. The median age at surgery was 66 days (IQR 45 – 116 days), and the mean body weight was 4 kg (3 – 5). Most (96%) attended all follow-up visits, and the average follow-up time was 37.4 months (8.4 – 69.3). There was 1 in-hospital death and 2 late mortalities. The 30-days and 5 years survival rate were 96% and 83%, respectively. One patient required conduit replacement at 3 years post operative because of conduit failure. The proportion of patients with freedom from conduit replacement at 5 years was 95%. Three cases required balloon dilatation of the left pulmonary artery due to stenosis. Freedom from all reinterventions and reoperations at 5 years was 52%. Definitive repair of this type of complex heart defect in small infants can be performed safely and resulted in good surgical outcomes.